A imprevisão como elemento caracterizador do interesse processual da ação revisional de aluguel na locação não residencial - Schewinsky, Juliana (2025)
This research seeks to analyze the unpredictability in the factual context as an existing element and driver of the review action of non-residential lease rental, this being an occasional characteristic, linked to the interest of the party to act and even if not provided for in the specific legislation, especially in distinction from the action provided for by the Tenant Law (Law No. 8,245/1991). The aforementioned action has a history of use before the courts, especially in times of crisis, such as the recent COVID-19 pandemic. In these cases, the Judiciary plays a decisive role in the application and circumstantial interpretation, taking into account the need to respect the preservation of the social function of the contract as well as the balance of interests in contractual relations, in the face of a situation of uncertain event. In this context, since the main factors that influence the increase in unpredictability are subjective elements that are not linked to the object agreed upon in the contract, the proportionality used by the judge in his/her free consent interferes with the requirements for filing the action and amplified interpretation of any interest in acting, increasing the exhaustive list typified for this type of action. These events affect the legal structure of the country, due to the fact that the State Powers, the jurisdictional powers, the citizens and the economy are closely linked. Furthermore, the aim is to better understand how contractual revisions based on the theory of unpredictability issued through judicial decisions operate. The aim is to distinguish the theory of unpredictability from other institutes of Civil Law that, at least initially, may be similar, bringing to light the main differences found. There is, however, a long way to go in order to ascertain any consequences on unpredictability and the interest in acting in the rent revision action